2018
DOI: 10.2147/cmar.s180389
|View full text |Cite
|
Sign up to set email alerts
|

Urine exosome gene expression of cancer-testis antigens for prediction of bladder carcinoma

Abstract: BackgroundExosomes have been regarded as emerging tools for cancer diagnosis. Tumor-derived exosomes contain molecules that enhance cancer progression and affect immune responses.Material and methodsIn the present study, we evaluated expression of seven cancer-testis antigens (CTAs) that are regarded as putative biomarkers and immunotherapeutic targets along with NMP22 in urinary exosomes of bladder cancer patients, healthy subjects and patients affected with nonmalignant urinary disorders.ResultsExosomal expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The interest in this panel of genetic biomarkers was later confirmed in another study that showed association to disease recurrence and poor prognosis [ 216 ]. Others studied the miRNA content of urinary EVs from BCa patients [ 217 , 218 , 219 , 220 , 221 ] and found miRNA signatures characteristic of high-grade BCa [ 216 , 220 ], which can be suggested as biomarkers of advanced disease. Interestingly, a study detailed one miRNA (miR-21-5p) overexpressed in urinary EVs of BCa patients with 75.0% sensitivity and 95.8% specificity for detecting disease, which was still present despite negative urinary cytology, suggesting it might detect BCa at an earlier stage of the disease, with no cytological changes [ 220 ].…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%
“…The interest in this panel of genetic biomarkers was later confirmed in another study that showed association to disease recurrence and poor prognosis [ 216 ]. Others studied the miRNA content of urinary EVs from BCa patients [ 217 , 218 , 219 , 220 , 221 ] and found miRNA signatures characteristic of high-grade BCa [ 216 , 220 ], which can be suggested as biomarkers of advanced disease. Interestingly, a study detailed one miRNA (miR-21-5p) overexpressed in urinary EVs of BCa patients with 75.0% sensitivity and 95.8% specificity for detecting disease, which was still present despite negative urinary cytology, suggesting it might detect BCa at an earlier stage of the disease, with no cytological changes [ 220 ].…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%
“…Interestingly, several CT antigens are also expressed in exosomes as well as the corresponding tumours. Melanoma-associated antigen (MAGE)-B4 showed higher gene expression in urinary exosomes from bladder cancer patients than that in normal control samples [129]. Testis-specific lactate dehydrogenase C4 was upregulated in serumal exosomes from breast cancer patients [130].…”
Section: Exosomal Expression Linked To Cancer Progression: Oncogenic mentioning
confidence: 98%
“…Yazarlou et al assessed the differential expression of seven cancer testis antigens and NMP22 between EVs (exosomes) derived from the urine of patients with BC, healthy controls and patients with benign urologic disease (Benign Prostate Hyperplasia; BPH, obstructive uropathy and bladder calculi). Results revealed that MAGE-B4 was upregulated in BC patients comparing to healthy controls and exosomal NMP 22 was higher in BC samples comparing to BPH [ 44 ].…”
Section: Evs As Biomarker Carriers For Bladder Cancer Diagnosismentioning
confidence: 99%